Determination of Phenolic and Flavonoid Content, Antioxidant and α-Amylase Inhibitory Activity of Leaf and Flower Extracts of Clerodendrum infortunatum and Hibiscus rosa sinensis Growing in Bara Nepal - Sharma, Khaga Raj; Thakur , Krishna (Journal of Balkumari College, 2022)
In the human body, oxidative stress imposed due to the increase in the concentration of free radicals such as reactive oxygen species (ROS) contributes to the initiation and progression of different diseases. The synthetic antioxidants have low efficacy with side effects, for that plant-derived natural antioxidant can prevent oxidative stress by reducing the risk of having these diseases. In the present study, the methanolic extracts of two traditionally used medicinal plants (leaf and flower) have tested for their antioxidant capacity, α-amylase enzyme inhibitory activity and determination of total phenolic and flavonoid content in the plant extracts. The antioxidant activity was evaluated by a 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay. The highest DPPH radical scavenging was shown by Clerodendrum infortunatum (IC50 = 71.95±0.51μg/mL) whereas leaf and flower of Hibiscus rosa sinensis showed moderate antioxidant activity (IC50 = 98.74±1.91 and 117.23±7.72 μg/mL) respectively. Among the tested plant extracts, the highest amount of total phenolic and flavonoid content was found in the methanolic extract of C. infortunatum with TPC of 87.07±9.22 mg GAE/g and TFC 34.40±2.00 mg QE/g. The antidiabetic activity of plant extracts was evaluated by the α-amylase enzyme inhibition assay. The leaf extract of C. infortunatum showed moderate α-amylase inhibition activity (IC50 = 118±4.80 μg/mL) whereas the standard acarbose has (IC50 = 12.96±0.22 μg/mL).